The Sabrina microfloras of East Antarctica: Late Cretaceous, Paleogene or reworked?. (2nd October 2021) - Macphail, Mike
Abstract: The published latest Palaeocene to Early–Middle Eocene age limits of the Sabrina microfloras, offshore Aurora Subglacial Basin, East Antarctica, largely depend on 1970s age-range data for fossil pollen and spore species in the continental margin basins of southern Australia. This paper uses updated biostratigraphical data from southern Australia, including the basins closest to the Aurora Basin throughout the Late Cretaceous and Paleogene, to propose that the age of the terrestrial component of the Sabrina microfloras is Campanian to Maastrichtian, not Paleogene. However, the revised age limits do not preclude these microfloras being redeposited more or less intact during the development and expansion of ice-sheets on East Antarctica, i.e. most probably during the late Paleogene based on other evidence from East Antarctica.